Are competitive interactions influenced by spatial nutrient heterogeneity and root foraging behavior? - Bliss, Kristin M (The New phytologist, 2002)
•  Nutrient heterogeneity, root foraging and competitive interactions were investigated for six species native to south-eastern USA. •  Monocultures, two- and six-species garden plots were fertilized to create spatially homogeneous or heterogeneous nutrient conditions. After 3.5 months, root proliferation in rich patches (precision), mean above-ground biomass per plant (scale) and influence of nutrient treatment on total plot biomass (sensitivity) in monocultures were measured. Competition (above-ground biomass) was assessed in two- and six-species plots. •  In monoculture plots, two species were relatively precise foragers, but no species showed significant sensitivity to nutrient treatment. Correlations between precision, scale and sensitivity were weak (-0.40 < r < 0.17), which contrasts with previous work showing a scale-precision trade-off. In two-species plots, competition was influenced by soil heterogeneity in two of six cases tested (anova, P < 0.05), and precise foragers grew larger in heterogeneous than in homogeneous conditions. In six-species plots, nutrient treatment had no influence on growth or competition. •  In our study system, heterogeneity effects on competition are context specific, generally weak and potentially mediated by the degree of root foraging precision